The impact of FDA regulatory activities on incident dispensing of LABA-containing medication: 2005–2011. (3rd August 2018) - Baker, Meghan A.; Butler, Melissa G.; Seymour, Sally; Zhang, Fang; Wu, Yute; Wu, Ann Chen; Levenson, Mark S.; Wu, Pingsheng; Iyer, Aarthi; Toh, Sengwee; Iyasu, Solomon; Zhou, Esther H.
ABSTRACT: Objective : Evidence of safety issues associated with long-acting beta2 -agonist (LABA) treatment has led to multiple regulatory activities by the U.S. Food and Drug Administration (FDA) on this class of medications. This study describes the impact of the regulatory activities on incident LABA-containing medication dispensing. Methods : A monthly rolling cohort of asthma patients who were eligible to initiate a LABA-containing product was created in the Mini-Sentinel Distributed Database between January 2005 and June 2011. Cohorts of individuals who initiated LABA were examined for the changes in the proportions of single-ingredient to fixed-dose inhaled corticosteroid (ICS)-LABA initiators, appropriate initiation of LABA-containing products, and use of controller medications. The impact of the 2005 and 2010 FDA regulatory activities associated with LABA-containing products was measured using interrupted time series with segmented regression. Results : LABA-containing product initiation was declining prior to the 2005 regulatory activities and continued to decline over the study period, accompanied by increased initiation of fixed dose ICS-LABA among LABA initiators. While the 2010 regulatory activities had no immediate impact on the proportion of LABA initiation in patients with prior controller medication dispensing and/or poor asthma control, there was an increasing positive trend toward LABA initiation in the appropriate patient population after the regulatory activities. Conclusion : The 2005 and 2010 FDA regulatory activities likely had an impact on communicating the safety concerns of LABA products. However, the impact cannot be viewed independent of scientific publications, guidelines for asthma treatment and other regulatory activities.